Star Wars: Anakin: Apprentice (Jedi readers. Step 4 book, ,, 2002)
Nineteen-year-old Anakin Skywalker, apprentice to Obi-Wan Kenobi, remembers some of his past adventures in which he raced swoop bikes, built androids, and found crystals to complete his lightsaber.